A232 EFFICACY OF TOFACITINIB FOR THE TREATMENT OF MODERATE-TO-SEVERE ULCERATIVE COLITIS: REAL-WORLD DATA. (26th February 2020) - Xiao, Y; Lakatos, P L; Bourdages, R; Bitton, A; Afif, W; Kohen, R; Berberi, M; Bessissow, T
Abstract: Background: A significant proportion of patients with moderate to severe ulcerative colitis (UC) do not respond to therapy, which includes thiopurines, glucocorticoids, and antagonists to tumour necrosis factor-α and integrin. Tofacitinib, a Janus Kinase inhibitor, has emerged as an efficacious and safe treatment for moderate to severe ulcerative colitis. However, it is not known if this efficacy translates into real-life effectiveness in a regular clinical practice. Aims: We aimed to assess the rate of clinical response and clinical remission at 3 and 6 months after tofacitinib initiation. Secondary endpoints included rate of biomarker normalization, corticosteroids-free clinical remission and severe infections. Methods: We conducted a multi-center retrospective observational study of adult patients with active UC started on tofacitinib from January 1, 2015 to October 1, 2019 at the McGill University Health Center and Hotel-Dieu de Lévis. A positive clinical response was defined as a decrease of ≥3 in the partial Mayo score. Clinical remission was defined as partial Mayo score of ≤2. Biomarker normalization was defined as fecal calprotectin ≤250ug/g. Severe infection was defined as an infection requiring hospitalization. Results: During the study period, 40 patients with UC were started on tofacitinib. Amongst the patients, 85% (n=34) had failed ≥1 biologic and 50% (n=20) had failed ≥3 biologics. At the time of this preliminary analysis, 38 patients had undergone 3 months of treatment and 30 patients had undergone 6 months of treatment. At 3 months, a clinical response was seen in 89.5% of patients (n=34) and clinical remission occurred in 63.2% (n=24). At 6 months, clinical response occurred in 73.3% of patients (n=22) and clinical remission was sustained in 53.33% (n=16). Biochemical normalization occurred in 29.0% (n=11) and 30.0% (n=9) at 3 and 6 months, respectively. Additionally, 63.2% (n=24) and 43.3% of patients (n=13) achieved steroid-free clinical remission at 3 and 6 months, respectively. In the interim, one patient developed a serious infection requiring discontinuation of drug. Conclusions: Our preliminary analysis demonstrates that in a real-life setting, tofacitinib is an effective treatment for inducing clinical remission in refractory UC patients. Further data will be complied to better assess the efficacy over a longer follow up. Funding Agencies: None